Findings at surveillance colonoscopy following surgery for colorectal cancer. Issue 3 (26th August 2016) - Udayasiri, Dilshan; Hollington, Paul
Abstract : Background: Colonoscopic surveillance following potentially curative surgery for colorectal cancer aims to detect treatable metachronous neoplasia. The timing and findings of colonoscopies for patients enrolled in an endoscopic surveillance programme were examined in this study. Methods: A retrospective clinical audit was undertaken of 174 consecutive patients undergoing surgery for first‐presentation colorectal cancer, looking at the findings of subsequent surveillance colonoscopies. Results: Sixty‐nine patients were fit for ongoing surveillance, with the median time to first colonoscopy being 14 months, and significant metachronous pathology was identified in 25%, comprising low‐risk adenomas, high‐risk adenomas, sessile serrated adenomas and one Dukes A carcinoma. Twenty‐seven patients underwent a second colonoscopy, with a median interval of 34 months between the investigations, and adenomas were identified in 30% of patients at the second surveillance colonoscopy. All polyps were colonoscopically resectable. Conclusion: Colonoscopy at 1 and 4 years following bowel cancer resection may detect treatable pathology in a significant proportion of those patients fit for ongoing surveillance.